Comparing Contact Education and Digital Distant Pedagogy Strategies: Lockdown Lessons Learnt for University-Level Teacher Education - Hannu Salmi; Ninja Hienonen; Laura Nyman; Arja Kaasinen; Helena Thuneberg (MDPI AG, 2023)
Teaching and learning experienced a rapid change in spring 2020, and the learning environments for university students changed almost overnight. An integrative science centre education informal learning course for Finnish teaching students has been arranged for over 20 years with latest technologies and innovations. This cross-sectional study compared survey data of teaching students between four time points: in 2019 (n = 108), in 2020 (n = 115), in 2021 (n = 110), and in 2022 (n = 90). The course content was the same, only the implementation differed. In the spring of 2019 and 2022 the course was implemented as contact-teaching, but during the critical phase of the pandemic in 2020 and 2021 as distant teaching. Data were analysed by using ANOVA and the prediction of possible effects of the contact/distance learning by the structural equation path model (SEM). The analysis showed that the results favoured the first contact instruction course in 2019: their confidence of integrating the learned contents of the science centre into practical school matters differed from all the other groups. This group also appreciated the usefulness of the course more than the other groups. In turn, the first distant course had a more negative opinion of the usability of the course than all the other groups. Despite that the distant group in 2020 and even more so the other distant group in 2021 felt more confidence in the direct integration of the course content into future teaching based on the path analysis. Gender had two kinds of effects, one in the distance learning group in 2020: being a female directly predicted the future use of science centre type pedagogy, and the other in the contact learning group in 2022: being a female predicted the appreciation of the science centre course. As a limitation of the study, more students' prior experience and attitudes with online learning is needed from future research. The preliminary results and best practises of this study are utilised internationally in several EU-Erasmus+ projects.